Pregnancy Outcomes with Intrahepatic Cholestasis - Ghias ul Hassan, Iram Inam, Saadia Sajjad (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: ICP is a reversible rare disorder prevailing in 2% of pregnancies resulting in debilitating feto-maternal consequences. Maternal problems resolves soon after delivery but fetal complications result in multiple deteriorations. Present study was undertaken to assess the pregnancy outcomes with ICP on both mother and fetus. Methodology: A prospective study design was used and study was conducted in tertiary health care sector in department of obstetrics and gynecology for period of 2 years. 80 mothers with history of pruritus, aminotransferase levels > 30 IU/L and alkaline phosphatase > 300 IU/L were included in this study. Pregnancies with other liver disorders were excluded. Study was conducted after institutional approval. Data was analyzed using SPSS version 23.0 and descriptive statistics were used to display the data in the form of frequency and percentages. Results: ICP accounted for many adverse feto-maternal outcomes. Results show sleep disturbance in 68.75%, PROM in 73%, risk of PPH 10% and 75.5% births were through operative method attributable to ICP. ICP caused fetus distress in 20% cases, MSL in 23.75% of babies, preterm birth (25%) and LBW babies (18.75%), rate of NICU admission (18.75%) and still birth revealed in 2.5% cases in this study. Conclusion: Present study depict the ill effects of ICP on both mother and fetus. Maternal effects are reversible but fetal effect cause permanent impairment for rest of fetus life. There is need for vigilant monitoring of the pregnant women affected with ICP to avoid such painful events.